A Hybrid Intelligent Controller for Extended-Range Electric Vehicles - Jayaraj, Jayakumar; Obulesu, Dakka; Govindaraj, Hemaprabha; Josh, Francisxavier Thomas; Rajeswaran, Nagalingam; Reddy, Chilakala Rami; Algarni, Abdullah S.; Alwabli, Abdullah; Malky, Saeed Faisal (Engineering, Technology & Applied Science Research, 2024)
A smart battery electric vehicle control framework is proposed in this paper. The specific controller empowers ceaseless observation and management of the battery’s state with the scope of extending the vehicle’s driving range under varying temperature and driving pattern conditions. The proposed method utilizes an incorporated scheme for dealing with a crossover energy stockpiling framework to expand a battery’s lifespan while further ensuring its smooth activity.